Assessing demand-side barriers to uptake of intermittent preventive treatment for malaria in pregnancy: a qualitative study in two regions of Uganda. (December 2016) - Rassi, Christian; Graham, Kirstie; King, Rebecca; Ssekitooleko, James; Mufubenga, Patrobas; Gudoi, Sam Siduda
Abstract Background To prevent malaria infection during pregnancy in endemic areas in Africa, the World Health Organization recommends the administration of intermittent preventive treatment in pregnancy (IPTp) as part of the focused antenatal care package. However, IPTp uptake in most countries remains low despite generally high antenatal care coverage and increased efforts by governments to address known bottlenecks such as drug stock-outs. The study explored factors that continue to impede uptake of IPTp among women who attend antenatal care. This paper focuses on demand-side barriers with regard to accessibility, affordability and acceptability. Methods The research was conducted in 2013/2014 and involved 46 in-depth interviews with four types of respondents: (i) seven district health officials; (ii) 15 health workers; (iii) 19 women who attended antenatal care; (iv) five opinion leaders. Interviews were conducted in Eastern and West Nile regions of Uganda. Data was analysed by thematic analysis. Results District health officials and health workers cited a range of barriers relating to knowledge and attitudes among pregnant women, including lack of awareness of pregnancy-related health risks, a tendency to initiate antenatal care late, reluctance to take medication and concerns about side effects of IPTp. However, women and opinion leaders expressed very positive views of antenatal care and IPTp. They also reported that the burden of travel and cost associated with antenatal care attendance was challenging, but did not keep them from accessing a service they perceived as beneficial. The role of trust in health workers' expertise was highlighted by all respondents and it was reported that women will typically accept IPTp if encouraged by a health worker. Conclusions Given the positive views of antenatal care and IPTp, high antenatal care coverage and reported low refusal rates for IPTp, supply-side issues are likely to account for the majority of missed opportunities for the provision of IPTp when women attend antenatal care. However, to increase uptake of IPTp on the demand side, health workers should be encouraged to reassure eligible women that IPTp is safe.